A Preliminary Study for the Development of a Somatic Experiencing-Based Interactive Family Play Therapy Program - Bo-kyeong Son; Hyun Sunwoo (Korean Association of Christian Counseling & Psychology, 2026)
This preliminary study aimed to develop a Somatic Experiencing (SE)-based Interactive Family Play Therapy (SE-IFP) program. By integrating SE theory and family play therapy theory and incorporating expert consultation, a preliminary program was developed. To examine its applicability, the six-session program was implemented with mother-child dyads from four families with children experiencing difficulties in emotion regulation, referred by local kindergartens. Data were collected through video recordings, observation logs, and mothers' reflection notes. In addition, the Emotion Regulation Checklist (ERC), parenting efficacy scales, and family play evaluations were administered before and after the intervention. Results indicated positive effects on children's emotion regulation, enhanced mothers' parenting efficacy, and positive changes in family interactions. These findings provide foundational data for developing an SE-based intervention using a bottom-up approach. Future studies should address limitations, including the small sample size and exclusive focus on mother-child dyads, to further refine the program for broader clinical application.